Application of Open Triple-Branched Aortic Arch Stent Graft for Acute Stanford Type A Aortic Dissection. (February 2013) - Hua, Fei; Shen, Zhenya; Yu, Yunsheng; Ye, Wenxue; Huang, Haoyue
Objective: Complete documentation is provided outlining a process for surgical treatment of the ascending aorta using open triple-branched aortic arch stent grafts to treat acute Stanford type A aortic dissection based on clinical observations. Methods: A total of 34 patients underwent replacement of the ascending aorta or aortic root in combination with open placement of a triple-branched stent graft. Results: Mean cardiopulmonary bypass, mean myocardial ischemic, and selective cerebral perfusion times were 186 ± 38, 101 ± 27, and 39 ± 11 minutes, respectively. Two deaths occurred during hospitalization. Of the remaining patients, postoperative computed tomography angiography confirmed that all implanted stent grafts were fully opened; however, the dissected aorta and false lumen size showed evidence of reduced thickness. Conclusions: This applies mainly to those who need extensive surgical reconstruction of the thoracic aorta with acute Stanford type A aortic dissection, and it can reduce cardiopulmonary bypass complexities of the traditional surgeries and potential complication.